Ca2+/Calmodulin-Dependent Protein Kinase- II in Vasoactive Peptide- Induced Responses and Vascular Biology - R. Simo Cheyou, Estelle; Bouallegue, Ali; K. Srivastava, Ashok (Current Vascular Pharmacology, 2014)
Vasoactive peptides such as angiotensin II and endothelin-1 as well as growth factors regulate vascular homeostasis through signaling pathways that are triggered in both normal and disease states. These vasoactive peptides and growth factors also increase the cellular levels of calcium which, through calcium binding effector systems initiating the downstream signaling and physiological responses in target cells. A multifunctional calcium-calmodulin-dependent protein kinase II (CaMKII) has emerged as an important transducer of vasoactive peptide-induced responses in vascular smooth muscle cells (VSMC). The catalytic activity of CaMKII can be stimulated by autophosphorylation and oxidation leading to the activation of signaling events that mediate growth, proliferation, migration, and gene transcription in VSMC. Pharmacological and gene deletion approaches have demonstrated a requirement of CaMKII in mediating the mitogen- activated protein kinase and phosphatidyl-inositol 3-kinase/protein kinase B signalling, as well as the proliferative, migratory and transcriptional responses of vasoactive peptides. In addition, a potential involvement of hyperactive CaMKII in animal models of vascular disease has also been reported. Therefore, this review aims to highlight the role of CaMKII in mediating signaling and physiological responses in VSMC and discuss its potential role in vascular pathophysiology.
Keywords: G-protein-coupled receptor